A hydrotalcite-derived indium-based catalyst and its preparation method and application
By performing high-temperature calcination and in-situ electrochemical reduction treatment on In-based hydrotalcite, a highly active, easy-to-industry hydrotalcite-derived indium-based catalyst was prepared, which solved the problems of complex synthesis and low yield of existing In-based catalysts, and significantly improved the CO2 reduction performance.
Patent Information
- Application Number
- CN202411547511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In-based catalysts in the prior art have problems such as complex synthesis steps, low yield and slow catalytic kinetics during the electrochemical CO2 reduction process to make formic acid.
By calcining the In-based hydrotalcite at high temperature and subjecting to in-situ electrochemical reduction treatment, a hydrotalcite-derived indium-based catalyst rich in defective structures and highly dispersed active components was prepared.
The catalyst exhibits high CO2 reduction reaction activity in a room temperature environment. Compared with the existing In2O3 materials, its performance has been significantly improved, and its preparation process is simple and easy to industrialize.
Smart Images

Figure CN119040951B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of CO2 electrochemical reduction, and in particular to a hydrotalcite-derived indium-based catalyst and a preparation method and application thereof. Background Art
[0002] Recycling and utilizing carbon dioxide (CO2) is a fundamental way to achieve carbon balance. Electrocatalytic CO2 reduction reaction (CO2RR) converts CO2 into carbon-containing products with commercial value by using electricity generated by clean renewable energy such as solar energy and wind energy. It can not only alleviate the energy crisis caused by the excessive use of fossil fuels, but also solve the environmental problems caused by excessive CO2 emissions. It has great advantages among many CO2 recovery strategies. Among the many products, recent technical and economic analysis shows that formic acid (HCOOH) is one of the most commercially viable products. The reaction pathway is simple, involving only the transfer of two electrons, and the electron utilization rate is high. In addition, HCOOH is an important organic chemical raw material, widely used in industries such as pesticides, leather, dyes, medicines and rubber. The industrial production of formic acid is usually achieved by carbonylation of methanol and subsequent hydrolysis of methyl formate. However, this process is energy-intensive, has a slow reaction rate and high investment cost. Therefore, how to convert carbon dioxide into formic acid gently and efficiently is of great significance. However, electrochemical CO2 reduction to formic acid still faces many challenges, such as difficulty in CO2 activation, poor stability, low formic acid selectivity, and competition with the hydrogen evolution reaction (HER). Therefore, it is urgent to develop economical, stable, and highly selective electrocatalytic materials.
[0003] In recent years, main group metal-based catalytic materials (including Bi, In, Sn and Pb, etc.) have shown high formic acid selectivity in the electrochemical CO2 reduction reaction. Among them, In-based metals are one of the promising catalytic materials for large-scale CO2 electroreduction to HCOOH due to their advantages such as environmental protection, inertness in hydrogen production and strong CO2 activation ability. However, In-based metal catalysts in the prior art have disadvantages such as complex synthesis steps, low yield and slow catalytic kinetics of electrocatalytic CO2 reduction to formic acid. Summary of the invention
[0004] The present invention is to overcome the above-mentioned problems of the In-based metal catalyst in the prior art, and to provide an indium-based catalyst derived from hydrotalcite and a preparation method and application thereof, wherein the In-based hydrotalcite is first calcined at high temperature to obtain a composite metal oxide of indium oxide, and then subjected to in-situ electrochemical reduction treatment, and finally an In-based catalyst rich in defective structure and highly dispersed active components is obtained, and the catalyst is used for electrocatalytic CO2 reduction conversion to produce formic acid / formate, and the In-based catalyst derived from hydrotalcite has a high reaction activity for electrocatalytic carbon dioxide reduction at room temperature, and its performance is significantly improved compared to the existing In2O3 material. In addition, the preparation of the indium-based hydrotalcite precursor is simple, and batch preparation can be achieved.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a hydrotalcite-derived indium-based catalyst, comprising the following steps:
[0007] (1) dissolving a soluble indium salt and a soluble divalent metal salt in water to obtain a mixed salt solution; dissolving sodium hydroxide and sodium carbonate in water to obtain an alkaline solution; and then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor to synthesize an indium-based hydrotalcite precursor; the soluble divalent metal salt is one or more of a magnesium salt, a zinc salt, and a copper salt;
[0008] (2) calcining the indium-based hydrotalcite precursor in an air atmosphere to obtain a composite metal oxide;
[0009] (3) The composite metal oxide is coated on the hydrophobic carbon fiber paper, and then subjected to in-situ electrochemical reduction treatment to obtain the hydrotalcite-derived indium-based catalyst.
[0010] Hydrotalcite is a layered double hydroxide (LDHs), the main layer of which is composed of divalent and trivalent metal ions and oxygen atoms forming octahedral edges. Since LDHs have rich adjustable properties, such as the type and proportion of layer metals, size and thickness, defect structure and coordination structure, the present invention first introduces active metal In into the layer of LDHs through step (1); then, through step (2), utilizes the topological transformation of LDHs to transform it into a composite metal oxide containing indium oxide; and then through step (3), combined with electrochemical reduction treatment, obtains an In-based catalyst rich in defect structure and highly dispersed active components.
[0011] The present invention uses indium-based hydrotalcite as a precursor to prepare an indium-based catalyst, which can not only achieve high dispersion of the active element indium, but also its rich heterogeneous interface structure can enhance the charge transfer of the reaction intermediates, thereby promoting catalytic activity. In addition, the present invention uses a rotating liquid film reactor to quickly synthesize the indium-based hydrotalcite precursor within a few minutes, and the synthesis process is simple and easy to achieve industrialization.
[0012] Preferably, in the mixed salt solution of step (1), the molar ratio of soluble divalent metal ions to indium ions is (1-6): 1. If too much or too little In ions are added, the hydrotalcite structure cannot be formed.
[0013] Preferably, in the alkaline solution of step (1), the molar ratio of sodium carbonate to indium ions is (1-4):1.
[0014] Preferably, the molar ratio of sodium hydroxide in the alkaline solution added in step (1) to the total metal ions in the mixed salt solution is (1-4):1.
[0015] Preferably, the rotation speed of the rotating liquid film reactor in step (1) is 3000-6000 r / min, and the reaction time of adding the mixed salt solution and the alkaline solution into the rotating liquid film reactor is 1-3 min.
[0016] Preferably, the calcination temperature in step (2) is 300-700° C., and the calcination time is 2-8 h.
[0017] Preferably, the loading amount of the composite metal oxide on the hydrophobic carbon fiber paper in step (3) is 0.1-2 mg / cm 2 .
[0018] Preferably, the in-situ electrochemical reduction treatment method in step (3) is one of linear sweep voltammetry (LSV) curve reduction, constant potential reduction and constant current reduction.
[0019] In a second aspect, the present invention provides a hydrotalcite-derived indium-based catalyst prepared using the above-mentioned preparation method.
[0020] In a third aspect, the present invention provides an application of a hydrotalcite-derived indium-based catalyst prepared by the above-mentioned preparation method in the electrocatalytic CO2 reduction reaction to produce formic acid.
[0021] Preferably, in the electrocatalytic CO2 reduction reaction to produce formic acid, a flow-type electrolytic cell system is used, with the hydrotalcite-derived indium-based catalyst as the working electrode, nickel foam as the counter electrode, Ag / AgCl as the reference electrode, and KOH solution as the electrolyte solution, CO2 gas is introduced, and then the reaction mixture is stirred at 50-300 mA / cm 2 The electrolysis was carried out at a current density of .
[0022] The indium-based catalyst of the present invention is used for electrocatalytic CO2 reduction, which is expected to reduce CO2 emissions and obtain HCOOH / HCOO -High value-added chemicals; at the same time, electrochemical operation is simple, reaction conditions are mild and controllable, raw materials can be recycled, reaction equipment can be modularized, and industrialization can be easily realized.
[0023] Preferably, the concentration of the KOH solution is 0.5-2 mol / L.
[0024] Therefore, the present invention has the following beneficial effects:
[0025] (1) The present invention uses indium-based hydrotalcite as a precursor to prepare an indium-based catalyst, which can not only achieve high dispersion of the active element indium, but also its rich heterogeneous interface structure can enhance the charge transfer of reaction intermediates, thereby promoting catalytic activity;
[0026] (2) The present invention uses a rotating liquid film reactor to quickly synthesize an indium-based hydrotalcite precursor within a few minutes. The synthesis process is simple and easy to realize industrialization;
[0027] (3) The indium-based catalyst derived from hydrotalcite of the present invention is used for electrocatalytic CO2 reduction, which is expected to reduce CO2 emissions and obtain HCOOH / HCOO - High value-added chemicals; the electrochemical operation is simple, the reaction conditions are mild and controllable, the raw materials can be recycled, the reaction equipment can be modularized, and it is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD test diagram of the indium-based hydrotalcite precursor prepared in Example 1.
[0029] Figure 2 This is the XRD test diagram of the composite metal oxide prepared in Example 1.
[0030] Figure 3 This is the XRD test pattern of the hydrotalcite-derived indium-based catalyst prepared in Example 1.
[0031] Figure 4 TEM images of the hydrotalcite-derived indium-based catalyst prepared in Example 1 at different magnifications.
[0032] Figure 5 is the element distribution diagram of the hydrotalcite-derived indium-based catalyst prepared in Example 1.
[0033] Figure 6 It is a linear voltammetric scanning curve diagram of the indium-based catalyst prepared in Example 1 and Comparative Example 1 under CO2 atmosphere.
[0034] Figure 7 1 is a comparison chart of the HCOOH Faraday efficiencies of the indium-based catalysts prepared in Example 1 and Comparative Example 1.
[0035] Figure 8 It is a comparison chart of the H2 and CO Faraday efficiencies of the indium-based catalysts prepared in Example 1 and Comparative Example 1.
[0036] Fig. 9 It is a comparison chart of the HCOOH Faraday efficiency of the indium-based catalysts prepared in Example 1 and Comparative Example 2.
[0037] Fig.10 It is a comparison chart of the H2 and CO Faraday efficiencies of the indium-based catalysts prepared in Example 1 and Comparative Example 2.
[0038] Fig.11 This is a test chart of the HCOOH, H2 and CO Faraday efficiencies of the indium-based catalyst prepared in Example 3. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0040] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0041] Overall embodiment:
[0042] A method for preparing a hydrotalcite-derived indium-based catalyst comprises the following steps:
[0043] (1) dissolving a soluble indium salt and a soluble divalent metal salt in water to obtain a mixed salt solution; dissolving sodium hydroxide and sodium carbonate in water to obtain an alkaline solution; and then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor to synthesize an indium-based hydrotalcite precursor; the soluble divalent metal salt is one or more of a magnesium salt, a zinc salt, and a copper salt;
[0044] (2) calcining the indium-based hydrotalcite precursor in an air atmosphere to obtain a composite metal oxide;
[0045] (3) The composite metal oxide is coated on the hydrophobic carbon fiber paper, and then subjected to in-situ electrochemical reduction treatment to obtain the hydrotalcite-derived indium-based catalyst.
[0046] As a specific implementation, in the mixed salt solution of step (1), the molar ratio of soluble divalent metal ions to indium ions is (1-6):1; preferably (2-3):1.
[0047] As a specific implementation, in the alkaline solution of step (1), the molar ratio of sodium carbonate to indium ions is (1-4):1.
[0048] As a specific implementation manner, the molar ratio of sodium hydroxide in the alkaline solution added in step (1) to the total metal ions in the mixed salt solution is (1-4):1.
[0049] As a specific implementation manner, the rotation speed of the rotating liquid film reactor in step (1) is 3000-6000 r / min, and the reaction time of adding the mixed salt solution and the alkaline solution into the rotating liquid film reactor is 1-3 min.
[0050] As a specific implementation, the calcination temperature in step (2) is 300-700° C., and the calcination time is 2-8 h.
[0051] As a specific implementation, the coating method of the composite metal oxide on the hydrophobic carbon fiber paper in step (3) is: dispersing the composite metal oxide and carbon black in a mixed solution of ethanol and 5-10wt% Nafion solution in a mass ratio of (1-5):1, and the volume ratio of ethanol to Nafion solution is 1000:10-30; after ultrasonic homogenization, drop-coat the solution on the hydrophobic carbon fiber paper and dry it naturally.
[0052] As a specific embodiment, the loading amount of the composite metal oxide on the hydrophobic carbon fiber paper in step (3) is 0.1-2 mg / cm 2 .
[0053] As a specific implementation, the in-situ electrochemical reduction treatment method in step (3) is one of linear sweep voltammetry (LSV) curve reduction, constant potential reduction and constant current reduction.
[0054] Embodiment 1:
[0055] A method for preparing a hydrotalcite-derived indium-based catalyst, comprising the following steps:
[0056] (1) dissolving indium nitrate pentahydrate and magnesium nitrate hexahydrate in water at a molar ratio of magnesium ion to indium ion of 2:1 to obtain a mixed salt solution; weighing sodium hydroxide and sodium carbonate at a total molar ratio of sodium hydroxide to indium ion and magnesium ion of 1.8:1 and a molar ratio of sodium carbonate to indium ion of 2:1 and dissolving them in water to obtain an alkaline solution; then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor at a rotating speed of 3000 r / min, reacting for 2 min, centrifuging the obtained precipitate, and washing with deionized water until the supernatant is neutral to obtain an indium-based hydrotalcite precursor;
[0057] (2) calcining the indium-based hydrotalcite precursor at 600°C for 4 h in an air atmosphere to obtain a composite metal oxide;
[0058] (3) The obtained composite metal oxide was coated on the hydrophobic carbon fiber paper (loading amount 1 mg / cm2 ) to obtain the working electrode. The specific coating method is as follows: 5 mg of composite metal oxide and 2.5 mg of carbon black are dispersed in 1 mL of ethanol and 20 μL of 5wt% Nafion solution, ultrasonically homogenized, and then 200 μL of the solution is dropped on a 1×1 cm 2 Hydrophobic carbon fiber paper, naturally dried;
[0059] (4) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (3) is used as a working electrode, and then LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the hydrotalcite-derived indium-based catalyst;
[0060] XRD tests were performed on the indium-based hydrotalcite precursor, the composite metal oxide and the indium-based catalyst derived from hydrotalcite obtained in Example 1. The results are as follows: Figure 1~Figure 3 As shown in . Figure 1 It can be seen that the indium-based hydrotalcite precursor exhibits characteristic diffraction peaks (003), (006), (009) and (110) belonging to LDHs; Figure 2 It can be seen that the composite metal oxide shows characteristic diffraction peaks attributable to MgO (222) and In2O3 (211), (222) and (400); this result indicates that the indium-based hydrotalcite precursor forms a composite metal oxide of MgO and In2O3 after calcination at 600 °C. Figure 3 It can be seen that the obtained hydrotalcite-derived indium-based catalyst exhibits characteristic diffraction peaks attributed to In elemental (101) and MgO (222).
[0061] The indium-based catalyst obtained in Example 1 was subjected to transmission electron microscopy and element distribution analysis. The results are as follows: Figure 4 and Figure 5 As shown in Figure 4 As shown in a, the hydrotalcite-derived indium-based catalyst prepared in the present invention is in the form of nanoparticles with a particle size of about 20 nm; Figure 4 The characteristic crystal planes of In element (101) and In2O3 (222) are shown in b, indicating that a heterogeneous interface structure of In / In2O3 exists in the structure of the hydrotalcite-derived indium-based catalyst prepared in the present invention. Figure 5 The energy spectrum shows that the Mg, In and O elements are evenly distributed in the hydrotalcite-derived indium-based catalyst prepared in the present invention;
[0062] (5) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50~300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO, H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of the products was calculated and analyzed; the results are shown in Table 1 and Figure 6~Figure 10 as shown in .
[0063] Embodiment 2:
[0064] A method for preparing a hydrotalcite-derived indium-based catalyst, comprising the following steps:
[0065] (1) dissolving indium nitrate pentahydrate and magnesium nitrate hexahydrate in water at a molar ratio of magnesium ion to indium ion of 3:1 to obtain a mixed salt solution; weighing sodium hydroxide and sodium carbonate at a total molar ratio of sodium hydroxide to indium ion and magnesium ion of 1.8:1 and a molar ratio of sodium carbonate to indium ion of 2:1 and dissolving them in water to obtain an alkaline solution; then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor at a rotating speed of 3000 r / min, reacting for 3 minutes, centrifuging the obtained precipitate, and washing with deionized water until the supernatant is neutral to obtain an indium-based hydrotalcite precursor;
[0066] (2) calcining the indium-based hydrotalcite precursor at 600°C for 4 h in an air atmosphere to obtain a composite metal oxide;
[0067] (3) The obtained composite metal oxide was coated on the hydrophobic carbon fiber paper (loading amount 1 mg / cm 2 ) to obtain the working electrode. The specific coating method is as follows: 5 mg of composite metal oxide and 2.5 mg of carbon black are dispersed in 1 mL of ethanol and 20 μL of 5wt% Nafion solution, ultrasonically homogenized, and then 200 μL of the solution is dropped on a 1×1 cm 2 Hydrophobic carbon fiber paper, naturally dried;
[0068] (4) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (3) is used as a working electrode, and then LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the hydrotalcite-derived indium-based catalyst;
[0069] (5) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50~300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO, H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of the products was calculated and analyzed; the results are shown in Table 1.
[0070] Embodiment 3:
[0071] A method for preparing a hydrotalcite-derived indium-based catalyst, comprising the following steps:
[0072] (1) dissolving indium nitrate pentahydrate and magnesium nitrate hexahydrate in water at a molar ratio of magnesium ion to indium ion of 2:1 to obtain a mixed salt solution; weighing sodium hydroxide and sodium carbonate at a total molar ratio of sodium hydroxide to indium ion and magnesium ion of 1.8:1 and a molar ratio of sodium carbonate to indium ion of 2:1 and dissolving them in water to obtain an alkaline solution; then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor at a rotating speed of 6000 r / min, reacting for 1 min, centrifuging the obtained precipitate, and washing with deionized water until the supernatant is neutral to obtain an indium-based hydrotalcite precursor;
[0073] (2) calcining the indium-based hydrotalcite precursor at 400°C for 4 h in an air atmosphere to obtain a composite metal oxide;
[0074] (3) The obtained composite metal oxide was coated on the hydrophobic carbon fiber paper (loading amount 1 mg / cm 2 ) to obtain the working electrode. The specific coating method is as follows: 5 mg of composite metal oxide and 2.5 mg of carbon black are dispersed in 1 mL of ethanol and 20 μL of 5wt% Nafion solution, ultrasonically homogenized, and then 200 μL of the solution is dropped on a 1×1 cm 2 Hydrophobic carbon fiber paper, naturally dried;
[0075] (4) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (3) is used as a working electrode, and then LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the hydrotalcite-derived indium-based catalyst;
[0076] (5) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50~300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO and H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of formic acid was calculated and analyzed; the results are shown in Table 1.
[0077] Embodiment 4:
[0078] A method for preparing a hydrotalcite-derived indium-based catalyst, comprising the following steps:
[0079] (1) dissolving indium nitrate pentahydrate and zinc nitrate hexahydrate in water at a molar ratio of zinc ion to indium ion of 2:1 to obtain a mixed salt solution; weighing sodium hydroxide and sodium carbonate at a total molar ratio of sodium hydroxide to indium ion and zinc ion of 1.8:1 and a molar ratio of sodium carbonate to indium ion of 2:1 and dissolving them in water to obtain an alkaline solution; then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor at a rotating speed of 5000 r / min, reacting for 2 min, centrifuging the obtained precipitate, and washing with deionized water until the supernatant is neutral to obtain an indium-based hydrotalcite precursor;
[0080] (2) calcining the indium-based hydrotalcite precursor at 600°C for 4 h in an air atmosphere to obtain a composite metal oxide;
[0081] (3) The obtained composite metal oxide was coated on the hydrophobic carbon fiber paper (loading amount 1 mg / cm 2 ) to obtain the working electrode. The specific coating method is as follows: 5 mg of composite metal oxide and 2.5 mg of carbon black are dispersed in 1 mL of ethanol and 20 μL of 5wt% Nafion solution, ultrasonically homogenized, and then 200 μL of the solution is dropped on a 1×1 cm2 Hydrophobic carbon fiber paper, naturally dried;
[0082] (4) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (3) is used as a working electrode, and then LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the hydrotalcite-derived indium-based catalyst;
[0083] (5) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50~300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO and H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of formic acid was calculated and analyzed; the results are shown in Table 1.
[0084] Comparative Example 1:
[0085] A method for preparing an indium-based catalyst comprises the following steps:
[0086] (1) Commercial In2O3 (Annaiji, particle size 80 nm) was coated on hydrophobic carbon fiber paper (loading amount 1 mg / cm 2 ) to obtain a working electrode, the coating method is the same as in Example 1;
[0087] (2) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (1) is used as a working electrode. Then, LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the indium-based catalyst.
[0088] (3) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow-type electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50-300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO, H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of the products was calculated and analyzed; the results are shown in Table 1 and Figure 6~Figure 8 as shown in .
[0089] Comparative Example 2:
[0090] A method for preparing an indium-based catalyst comprises the following steps:
[0091] (1) Commercial In2O3 (Annaiji, particle size 80 nm) and MgO (particle size 20-50 nm) with a mass ratio of 7.4:2.6 were coated on hydrophobic carbon fiber paper (total loading of In2O3 and MgO 1 mg / cm 2 ) to obtain a working electrode, the coating method is the same as in Example 1;
[0092] (2) In a three-electrode system, a Pt electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the electrode in step (1) is used as a working electrode. Then, LSV electrochemical reduction is performed in a CO2-saturated 0.5 mol / L KHCO3 electrolyte solution at 0 to -2 V (vs. Ag / AgCl) until the LSV curve remains substantially unchanged, thereby obtaining the indium-based catalyst.
[0093] (3) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow-type electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50-300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO, H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of the products was calculated and analyzed; the results are shown in Table 1 and Fig. 9 and Fig.10 as shown in .
[0094] Comparative Example 3:
[0095] A method for preparing an indium-based catalyst comprises the following steps:
[0096] (1) In particles (Annaiji, particle size 200 nm) were coated on hydrophobic carbon fiber paper (loading amount 1 mg / cm 2 ), to obtain the indium-based catalyst; the coating method is the same as in Example 1;
[0097] (2) The electrocatalytic CO2 reduction performance of the indium-based catalyst prepared above was tested in a typical flow-type electrolytic cell system. The method was as follows: the prepared indium-based catalyst was used as the working electrode, nickel foam was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 1 mol / L KOH solution was used as the electrolyte solution. 20 mL / min of CO2 gas was introduced, and then the reaction mixture was stirred at different current densities (50-300 mA / cm 2 ) for 30 minutes; gaseous products (such as CO, H2) were detected by gas chromatograph (Shimadzu GC-2014), liquid products were detected by liquid chromatograph (Agilent 1260-Infinity II), and the Faraday efficiency of the products was calculated and analyzed; the results are shown in Table 1 and Fig.11 as shown in .
[0098] Table 1: Test results of electrocatalytic CO2 reduction performance
[0099]
[0100] from Figure 6~Figure 8 It can be seen that compared with the catalyst directly using commercial In2O3 for electrochemical reduction in Comparative Example 1, the hydrotalcite-derived indium-based catalyst in Example 1 shows higher Faraday efficiency of HCOOH and lower H2 selectivity in a wide current range. This is because the active element In in the hydrotalcite-derived indium-based catalyst prepared by the method of the present invention in Example 1 is highly dispersed and has more highly exposed In / In2O3 heterojunction interface structures, and the introduction of MgO promotes the adsorption of CO2 and increases the local concentration of CO2 on the surface.
[0101] from Fig. 9 and Fig.10It can be seen that compared with the physically mixed MgO and In2O3 in Comparative Example 2, the hydrotalcite-derived indium-based catalyst prepared by the method of the present invention in Example 1 exhibits higher formic acid selectivity in a wide current density range. This is because there is a mutual coupling effect at the phase interface of Re-MgMn-MMO derived from hydrotalcite, which is beneficial to the charge transfer in the CO2 reduction process, thereby improving the reaction performance.
[0102] from Fig.11 It can be seen that the elemental In particle catalyst in Comparative Example 3 exhibits lower formic acid selectivity in a wide current density range compared with the hydrotalcite-derived indium-based catalyst prepared by the method of the present invention in Example 1.
[0103] Therefore, combining Table 1 and Figure 6~Figure 11 It can be seen from the data in that the indium-based catalyst derived from hydrotalcite prepared by the method of the present invention has better performance in the electrocatalytic reduction of CO2 to formic acid. The present invention uses indium-based hydrotalcite as a precursor to prepare an indium-based catalyst, which can not only achieve high dispersion of the active element indium, but also its rich heterogeneous interface structure can enhance the charge transfer of reaction intermediates, thereby promoting catalytic activity; at the same time, the present invention uses a rotating liquid film reactor to quickly synthesize the indium-based hydrotalcite precursor within a few minutes, and the synthesis process is simple and easy to industrialize. The application of the indium-based catalyst derived from the hydrotalcite in the present invention to the electrocatalytic reduction of CO2 is not only expected to reduce CO2 emissions, but also to obtain HCOOH / HCOO - High value-added chemicals. The electrochemical operation is simple, the reaction conditions are mild and controllable, the raw materials can be recycled, the reaction device can be modularized, and it is easy to realize industrialization.
[0104] Although specific embodiments have been used to illustrate the invention, it is understood that the above embodiments are used to understand the methods and core matters of the present invention and cannot be understood as limitations on the present invention. A person of ordinary skill in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention. Any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for preparing a hydrotalcite-derived indium-based catalyst, characterized in that: The steps include: (1) dissolving a soluble indium salt and a soluble divalent metal salt in water to obtain a mixed salt solution, wherein the molar ratio of soluble divalent metal ions to indium ions in the mixed salt solution is (1-6):1; dissolving sodium hydroxide and sodium carbonate in water to obtain an alkaline solution; and then simultaneously adding the mixed salt solution and the alkaline solution into a rotating liquid film reactor to synthesize an indium-based hydrotalcite precursor; the soluble divalent metal salt is one or more of a magnesium salt, a zinc salt, and a copper salt; (2) calcining the indium-based hydrotalcite precursor in an air atmosphere to obtain a composite metal oxide; (3) The composite metal oxide is coated on the hydrophobic carbon fiber paper, and then subjected to in-situ electrochemical reduction treatment to obtain the hydrotalcite-derived indium-based catalyst.
2. The method for preparing a hydrotalcite-derived indium-based catalyst according to claim 1, characterized in that: In the alkaline solution of step (1), the molar ratio of sodium carbonate to indium ions is (1-4):
1.
3. The method for preparing a hydrotalcite-derived indium-based catalyst according to claim 1 or 2, characterized in that: The molar ratio of the sodium hydroxide in the alkaline solution added in step (1) to the total metal ions in the mixed salt solution is (1-4):
1.
4. The method for preparing a hydrotalcite-derived indium-based catalyst according to claim 1, characterized in that: In step (1), the rotation speed of the rotating liquid film reactor is 3000-6000 r / min, and the reaction time of adding the mixed salt solution and the alkaline solution into the rotating liquid film reactor is 1-3 min.
5. The method for preparing a hydrotalcite-derived indium-based catalyst according to claim 1, characterized in that: The calcination temperature in step (2) is 300-700° C., and the calcination time is 2-8 hours.
6. The method for preparing a hydrotalcite-derived indium-based catalyst according to claim 1, characterized in that: The loading amount of the composite metal oxide on the hydrophobic carbon fiber paper in step (3) is 0.1-2 mg / cm 2 .
7. A hydrotalcite-derived indium-based catalyst, characterized in that: It is prepared using the preparation method described in any one of claims 1 to 6.
8. Use of the hydrotalcite-derived indium-based catalyst as claimed in claim 7 or the hydrotalcite-derived indium-based catalyst prepared by the preparation method as claimed in any one of claims 1 to 6, characterized in that: Applied to the electrocatalytic CO2 reduction reaction to produce formic acid.
9. The use of the hydrotalcite-derived indium-based catalyst according to claim 8, characterized in that: In the electrocatalytic CO2 reduction reaction to produce formic acid, a flow-type electrolytic cell system is used, with the hydrotalcite-derived indium-based catalyst as the working electrode, nickel foam as the counter electrode, Ag / AgCl as the reference electrode, and KOH solution as the electrolyte solution, CO2 gas is introduced, and then the reaction mixture is stirred at 50-300 mA / cm 2 The electrolysis was carried out at a current density of .
Citation Information
Patent Citations
Indium-indium trioxide heterogeneous nano-material composite electrocatalyst as well as preparation method and application thereof
CN111632587A
Indium-based hydroxide catalyst for preparing formic acid through electro-catalysis of carbon dioxide as well as preparation method and application of indium-based hydroxide catalyst
CN116103682A